اسلامی بینکاری و مالیات کی ترویج :پروفیسر ڈاکٹر محمود احمد غازی ؒ کی خدمات کا جائزہ - Habib Ur Rehman; Muhammad Asghar Shahzad (Pakistan Journal of Islamic Research)
The end of the twentieth century and the beginning of the 21st century witnessed many intellectual and academic contributions in the field of Islamic Sciences. Dr. Mahmood Ahmad Ghazi (d. 2010), a renowned scholar of Islamic law and jurisprudence, Islamic Finance played a very significant role in the process of Islamization of laws and the economy in Pakistan. His contribution to Islamization of economics and financial system as an academician, Judge, member council of Islamic Ideology, member Commission for Islamization of Economy (CIE) and member Sharī’ah supervisory Board in State Bank of Pakistan, Takaful Pakistan and Bank of Khyber. The main objective of this paper is to focus on the efforts and contributions of Dr. Mahmood Ahmad Ghazi regarding Islamic Economics, Islamic Banking, and finance.